2020
DOI: 10.1038/s41467-020-19988-z
|View full text |Cite|
|
Sign up to set email alerts
|

The transcriptome of circulating sexually committed Plasmodium falciparum ring stage parasites forecasts malaria transmission potential

Abstract: Malaria is spread by the transmission of sexual stage parasites, called gametocytes. However, with Plasmodium falciparum, gametocytes can only be detected in peripheral blood when they are mature and transmissible to a mosquito, which complicates control efforts. Here, we identify the set of genes overexpressed in patient blood samples with high levels of gametocyte-committed ring stage parasites. Expression of all 18 genes is regulated by transcription factor AP2-G, which is required for gametocytogenesis. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…at least daily) measurements improve conversion rate estimates because variable multiplication and mortality rates of asexuals, mortality of gametocytes, and RBC dynamics can be accounted for. Furthermore, the earlier that gametocytes/sexually committed parasites are detected [ [68] , [69] , [70] , [71] ], the less opportunity gametocyte mortality has to bias conversion estimates. Finally, the recent discovery that parasites may not always commit to sexual conversion in the IDC before conversion takes place (next cycle conversion, NCC, Fig.…”
Section: Complex Conversion Ratesmentioning
confidence: 99%
“…at least daily) measurements improve conversion rate estimates because variable multiplication and mortality rates of asexuals, mortality of gametocytes, and RBC dynamics can be accounted for. Furthermore, the earlier that gametocytes/sexually committed parasites are detected [ [68] , [69] , [70] , [71] ], the less opportunity gametocyte mortality has to bias conversion estimates. Finally, the recent discovery that parasites may not always commit to sexual conversion in the IDC before conversion takes place (next cycle conversion, NCC, Fig.…”
Section: Complex Conversion Ratesmentioning
confidence: 99%
“…In addition, the sensitivity of the pfpeg4 and pfg27 RT-qPCR (190 and 390 gametocytes per mL of blood, respectively) is comparable to that reported in other assays for gametocyte specific markers, such as the female ( pfs25 ) and male ( pfs230p ) gametocyte specific RT-qPCR assays, with a detection limits of 0.3 female and 1.8 male gametocytes/µL blood, respectively 56 . Similar RT-qPCR assays for putative early gametocyte markers (ap2-g, surfin 13.1, and surfin 1.2), have been described with a similar low limit of detection (2 gametocytes/µL blood), a level below the level theoretically required to infect a mosquito 49 .…”
Section: Discussionmentioning
confidence: 65%
“…The authors reported a high proportion of infections with circulating sexually-committed ring stage parasites (76%), but the ratio of gametocytes to sexually committed rings (in vitro) varied dramatically, ranging from 78% to absent. Prajapati et al 49 also reported a high prevalence (57.14%) of early gametocytes in children with asymptomatic P. falciparum infection in Ghana. Although gametocytes were not quantified in these reports, the pattern of detection of early gametocytes is consistent with that seen in our field setting in eastern Sudan, where 83.8% of infected individuals contained transcripts of early gametocyte stages ( pfpeg4 and/or pfg27 ).…”
Section: Discussionmentioning
confidence: 94%
“…Given the importance of genetic variation for vaccine and drug efficacy, reliance on a single parasite isolate fails to give a comprehensive insight into intervention potency in natural infections [ 10 ]. Similarly, relevant inter-strain variation in parasite growth rates [ 11 ], gametocyte production [ 12 ] and sporozoite invasion capacity [ 13 , 14 ] warrant further examination. The current portfolio of laboratory isolates for studies on sexual and sporogonic stages is very limited.…”
Section: Introductionmentioning
confidence: 99%